(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Polyherbal preparations have been used for health management for decades. Allopathic dosage forms are prominent due to their ease of administration and stability, but polyherbal formulations are also pharmacologically effective and show useful therapeutic activity. As a result, extracts of a six potent herbs with anti-oxidant and anti-hypertensive properties were chosen and formulated in a capsule dosage form. This study aims to investigate the anti-oxidant activity of a polyherboceutical formulation. A polyherboceutical formulation were prepared using six ingredients, and quality control parameters were performed, including organoleptic, physio-chemical, qualitative, and quantitative estimation of secondary metabolites and microbial load. The formulation was possessed a good anti-oxidant activity with 7.87 mg/mL for IC50 and 0.5 of absorbance on 8.6 mg/mL concentration found with DPPH free radical scavenging activity and ferric-ion reducing activity simultaneously.